Marcela Labraña. Ensayos sobre el silencio. Gestos, mapas y colores. Madrid: Siruela, 2017 - Schoennenbeck, Sebastián (Estudios Avanzados, 2017)
Marcela Labraña. Ensayos sobre el silencio. Gestos, mapas y colores. Madrid: Siruela, 2017